2021
DOI: 10.3390/admsci11010030
|View full text |Cite
|
Sign up to set email alerts
|

Family Firms and Coupling among CSR Disclosures and Performance

Abstract: This paper aims to analyse the behaviours related to the decoupling of the disclosed information on Corporate Social Responsibility (CSR) and corporate sustainability, deepening these practices’ knowledge within family businesses. For this purpose, we defined decoupling as a gap between social responsibility performance (internal actions) and disclosures (external actions). For a sample of 33,809 observations for the period 2011–2019, corresponding to 5029 companies, 19% being family firms, our empirical evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…According to the theory of social psychology, self-verification is typical of managers who want to be known and understood by others according to their firm beliefs and feelings about themselves, including their sense of self and self-esteem. Similar results were obtained by Phan et al [91], García-Sánchez et al [92], Melón-Izco et al [93], Capela-Borralho et al [94] and Parra-Domínguez et al [95], authors who found the existence of a neutral discourse when companies report on their commitments to the 2030 Agenda, the content of management report or a CSR coupling in the case of family firms reporting.…”
Section: Discussion Of Resultssupporting
confidence: 81%
“…The results, reflected in the third and fourth columns, allow us to observe that the effect of the adoption of the GRI standards makes it possible to reduce underperformance practices but has no effect on underdisclosure strategies. Firms that adopt silent practices may be omitting certain information so that their stakeholders do not create expectations that companies cannot meet later, and they cannot be accused of hypocrisy (Parra-Domínguez et al, 2021).…”
Section: Ta B L Ementioning
confidence: 99%
“…Later, we create a dummy variable that takes the value of 1 for those firms whose EnvGap is higher than 0 due to the companies having implemented more environmentally responsible policies and actions that they disclose in their reports. This procedure is used by Parra-Domínguez et al (2021). In Table 5, it can be observed that the most innovative companies from the environmental point of view are very likely to adopt strategies of silence in their reports in relation to certain information on their environmental performance (EnvInno: Coeff.…”
Section: Complementary Analysismentioning
confidence: 99%